ANALISIS STUDI KELAYAKAN BISNIS DALAM PENGEMBANGAN UMKM KOTA BATAM PADA USAHA BUNBUN COOKIES AND CAKES - Wahyudi Ilham (PUSLITABMAS - BATAM TOURISM POLYTECNIC, 2023)
Bunbun Cookies and Cakes, a processed food company, aims to contribute to the growth of micro, small, and medium-sized enterprises (MSMEs) in Batam City, recognizing their crucial role in Indonesia's economy. To assess the viability of the business launch, a comprehensive feasibility study was conducted. Employing a qualitative approach with descriptive methods, the study's objective was to determine the feasibility of Bunbun Cookies and Cakes. Rather than relying solely on a single criterion, the evaluation considered various aspects, each requiring specific values for feasibility. The assessment encompassed legal, environmental, market, technology/technical, management/human resources, and financial dimensions. The study's findings indicate that the Bunbun Cookies and Cakes business is not only feasible but also holds promising prospects for success.